Constitution writing, religion and democracy / edited by Asli U. Bali, University of California, Los Angeles, Hanna Lerner, Tel-Aviv University, Israel. - Bali, Asli Ümmühan, 1971-; Lerner, Hanna (Cambridge University Press, 2017)
What role do and should constitutions play in mitigating intense disagreements over the religious character of a state? And what kind of constitutional solutions might reconcile democracy with the type of religious demands raised in contemporary democratising or democratic states? Tensions over religion-state relations are gaining increasing salience in constitution writing and rewriting around the world. This book explores the challenge of crafting a democratic constitution under conditions of deep disagreement over a state's religious or secular identity. It draws on a broad range of relevant case studies of past and current constitutional debates in Europe, Asia, Africa and the Middle East, and offers valuable lessons for societies soon to embark on constitution drafting or amendment processes where religion is an issue of contention.